Terrorism Deradicalization Management Based on Education on the Principles of Islamic Teaching - Sholehuddin Sholehuddin; Gofur Ahmad; Rohimi Zam Zam (Yayasan Adra Karima Hubbi, 2024)
Background. This research was motivated by the researcher's academic anxiety, namely the existence of a gap in the implementation of deradicalization. The deradicalization currently being carried out by the government, whether through the BNPT, Densus 88 AT Polri, the Directorate General of Corrections or community groups is not well organized, especially regarding the role of institutions, materials (clarification of several points of Islamic teachings that are often misinterpreted) and delivery approaches. This shows the importance of a more in-depth study of how to manage the deradicalization of terrorism based on basic Islamic teachings so that it can run in a programmed, targeted and sustainable manner. Purpose. This research aims to describe, analyze and discover the concept of implementation and management of terrorism deradicalization. This research answers two main problems, namely first how to conceptualize deradicalization and second how to implement deradicalization management. Method. This research was conducted with a qualitative approach using grounded theory designs. The data sources are former terrorism convicts, perpetrators of acts of terrorism, deradicalization implementers from both government agencies and community groups. Results. The results of this research show that from an Islamic perspective, the concept of deradicalization refers to the An-Nahl letter. 16: 119 which consists of four pillars, namely recognition as a mistake, a statement or pledge not to do it again or repent, an apology to the affected party, and a commitment to improvement. In the management review, the deradicalization program has not been managed optimally based on management functions (planning, organizing, actuating and controlling). Conclusion. It is hoped that this research will be useful for deradicalization stakeholders so that the deradicalization process can be managed in a more programmed, targeted and sustainable manner. This research can also be useful for academic circles for the development of knowledge, insight and further research.